2011
DOI: 10.1093/icvts/ivr019
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative serum troponin I levels are associated with higher risk for atrial fibrillation in patients undergoing coronary artery bypass graft surgery

Abstract: Atrial fibrillation (AF) remains a frequent complication after coronary artery bypass graft surgery (CABG). We evaluate the association of AF occurrence and serum cardiac troponin I (cTnI) levels in the early postoperative period after CABG. Between April 2009 and January 2010, 95 consecutive patients with sinus rhythm who underwent CABG were evaluated. The patients were divided into two groups according to their postoperative rhythms: sinus rhythm group (SR) and AF group (AF). Demographic, clinical variables,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
0
11
3
Order By: Relevance
“…Although we found no association between cTnI and postoperative AF and did not detect a cut-off value of cTnI which was able to distinguish the patients at high-risk for AF occurrence, Leal et al [14] included 95 patients who exclusively underwent CABG showed that postoperative cTnI levels were associated with the AF occurrence after CABG. The authors also found a cut-off value of 0.901 ng/ mL of cTnI after surgery, which was able to identify high-risk patients for postoperative AF.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Although we found no association between cTnI and postoperative AF and did not detect a cut-off value of cTnI which was able to distinguish the patients at high-risk for AF occurrence, Leal et al [14] included 95 patients who exclusively underwent CABG showed that postoperative cTnI levels were associated with the AF occurrence after CABG. The authors also found a cut-off value of 0.901 ng/ mL of cTnI after surgery, which was able to identify high-risk patients for postoperative AF.…”
Section: Discussioncontrasting
confidence: 88%
“…[12,13] The pathogenesis of postoperative AF is multifactorial and includes preoperative, perioperative, and postoperative factors such as gender, age, hypertension, DM, hyperlipidemia, chronic renal failure, ejection fraction, number of grafts performed, left atrial enlargement, acute atrial dilatation, atrial injury caused by cannulation, RCA stenosis, CPB run length, cross-clamping time, electrolyte imbalance, and pericarditis. [2,5,[14][15][16][17] However, in this study, we found no association between these variables and postoperative AF development. Among these factors, age was documented to be the most reliable predictor for postoperative AF.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…To date, contradictory results have been published regarding the value of elevated TnI levels to predict AF in the post-operative setting after coronary artery bypass graft surgery. 34 There have been few reports on the predictive utility of hsTnI for AF in community- or hospital-based settings. One small community-based Japanese study including 220 residents without apparent cardiovascular disease reported that hsTnT concentrations were higher in the 12 (6%) patients with AF at health checkup examination than in those without AF.…”
Section: Discussionmentioning
confidence: 99%
“…As we known that cardiac troponin displayed powerful prognostic properties in patients with AF, with almost a 2-fold increase of stroke risk and more than a 3-fold increase of cardiovascular mortality when AF patients had elevated versus undetectable levels were compared. Leal et al have shown that the higher cTnI serum levels were detected in patients who developed AF at the postoperative period after CABG [Leal 2012]. Thus, when we detected high cardiac biomarkers such as cardiac TnI and CK-MB after CABG, we followed the patients for a long time after discharge from the hospital.…”
Section: E292mentioning
confidence: 93%